Predictors of parental involvement in Malaysian secondary schools - Keetanjaly, A.; Abdul Kadir, Suhaida; Wong, Su Luan; Abdullah, Arnida (Universiti Putra Malaysia Press, 2020)
Past literature points to the fact that the extent of parental involvement in school increases the level of a child’s ability and independence in studies during the child’s schooling years. The present study investigated the predictors of parental involvement in selected regular secondary schools in Malaysia. The participants of the study were class teachers who had been teaching for more than two years, were selected from 40 schools located in Peninsular Malaysia. A cross-sectional and descriptive study using postal-based survey methods was conducted on a sample of 373 secondary school class teachers. Mediation analysis was conducted using the PROCESS macro with the aim of investigating the relationships between the variables. The findings revealed that the association between the role of creativity in principals’ leadership practices and parental involvement in secondary schools was mediated by collaborative school practices and school climate. Further analysis revealed that the mediated model had a moderate effect on parental involvement in secondary schools. It is, therefore, necessary for secondary school leaders to consider and implement innovative programmes that take into account the important role of increasing parental involvement in the process of transformation.